Wild pink bayberry free phenolic extract induces mitochondria-dependent apoptosis and G0/G1 cell cycle arrest through p38/MAPK and PI3K/Akt pathway in MDA-MB-231 cancer cells - Wen Xia; Er-sheng Gong; Yanyun Lin; Bisheng Zheng; Wenhan Yang; Tong Li; Sheng Zhang; Peng Li; Rui-hai Liu (Food Science and Human Wellness)
Polyphenol-rich foods have been shown to be good for cancer prevention as powerful antioxidants. In this study, the mechanisms of wild pink bayberry free phenolic extract (WPBFE) inhibiting the proliferation and inducing apoptotic of MDA-MB-231 breast cancer cells was examined. The main phenolic acids and flavonols in WPBFE were gallic acid ((18.83 ± 0.44) μg/g FW) and myricetin ((1.52 ± 0.05) μg/g FW), respectively. The maximum inhibition rate of WPBFE at non-cytotoxicity dose (below 80 mg/mL) was 81 %. Western blotting analysis showed that WPBFE could cause the arrest of cell cycle in G0/G1 phase by down-regulating expression levels of PCNA, CDK4, cyclin D1 and up-regulating the expression level of p21. Meanwhile, WPBFE induced apoptosis through initiating the mitochondrial death pathway by up-regulating cleaved caspase-3 and enhancing the ratio of Bax/Bcl-2, with the maximum expression levels of 1.29 and 2.03 folds that of control group, respectively. Further study of the upstream protein, we found that WPBFE down-regulated TRAF2, while upregulated p-ASK1, p-p38 and p-p53. Furthermore, WPBFE could down-regulate the expression of p-PI3K and p-Akt. These observations indicated that WPBFE might play an anticancer role through regulating the p38 MAPK together with PI3K/Akt pathway.